Corrigendum: 14-3-3ζ regulates the mitochondrial respiratory reserve linked to platelet phosphatidylserine exposure and procoagulant function - Schoenwaelder, S.; Darbousset, R.; Cranmer, S.; Ramshaw, H.; Orive, S.; Sturgeon, S.; Yuan, Y.; Yao, Y.; Krycer, J.; Woodcock, J.; Maclean, J.; Pitson, S.; et al. (Macmillan Publishers Limited, 2017)
This corrects the article DOI: 10.1038/ncomms12862.